Pengaruh Modal, Luas Lahan Dan Tenaga Kerja Terhadap Pendapatan Usahatani Padi (Oryza sativa L.) Kultivar Mekongga (Suatu Kasus di Kecamatan Haurwangi Kabupaten Cianjur) - Asep Haryanto; Euis Dasipah; Adjat Sudradjat (OrchidAgri, 2021)
This study aims to determine the effect of variable capital, land area and labor variables on rice farming income. The sample studied was 115 respondents in Haurwangi District, Cianjur Regency. The method used in this research is a survey method, with the rice farmer analysis unit, taking samples from the entire population by means of a questionnaire as a means of collecting basic data. The definition of survey here is limited to the definition of a census sample survey to obtain the necessary information and collected from all populations in the research location. The analysis design used is multiple regression linear analysis. The data obtained were processed using SPSS version 21 For Windows. The results showed that: 1) Multiple regression, simultaneously the variables of capital and labor to income have a significant effect. Income is influenced by capital and labor by 99.9%, while the remaining 0.1% is influenced by other factors not examined in this study. Partially the capital variable and the labor variable affect the income of rice farming. The β values for the capital variable and the labor variable are 1.178 and 66.178.541, respectively. Shows that there is a real relationship between the independent and dependent variables; 2) Land area variable because it does not have a significant effect on farm income, the calculation is excluded.